Structural modification of ultra-thin Fe films on Cu(100) prepared by pulsed laser deposition - Weinelt, Martin; Baier, Holger; Schwarz, Sergej; Fauster, Thomas (Surface Science, 2000)
The structure and quality of ultra-thin iron films on Cu(100) prepared by pulsed laser deposition (PLD) were studied by means of low energy electron diffraction (LEED). As in the case of thermal deposition (TD), the film undergoes a structural transition from a tetragonally expanded phase to the undistorted fee structure at an iron coverage of 5 monolayers (ML). The changed structure of the Fe/Cu interface and the improved film quality are discussed in terms of the laser-fluence dependency of the deposited particle energies for PLD. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: laser methods; low energy electron diffraction (LEED); metal-metal magnetic thin film structures